Humanising healthcare spaces through culture: design of labour delivery room for the Malay-Muslim community as case study - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton (2015)
Modern man and women have lived in the medicalised world from birth till death with the advent of modern sciences brought about into the healthcare environment. Culture as a way of life of an ordinary man suddenly stops as one enters the alien world of modern healthcare where certain expected behavioural standards are required. Many research were made to humanise healthcare environment so as to soften this clashes with the environment. Some reforms were made in the waiting areas, inpatient accommodations and other public areas of the healthcare facility to be people friendly. However, there are still very little inroads made to humanise the clinical areas of the healthcare environment apart from interior decoration and spatial layout. Malaysia had awakened from its colonial days and had accepted the fact that traditional medicine lives in a separate stream from mainstream modern medicine as alternative choices. Birthing as a normal event, however, has been brought into modern healthcare from its traditional setting to save lives of both mother and child. In doing so, the cultural environment and shared values of celebrating new lives are taken away from the mother and the family to a sterile and clean environment where the mother is no longer in charge of her needs. The objective of this research is to humanise the clinical spaces of the modern healthcare environment using labour delivery room as the case study and the Malay Muslim culture as the humanising factor. The methodology adopted for the research is both qualitative and quantitative. Explorative and experimental designs using empirical data gathered from primary and secondary sources were made based on findings and comparative analysis of the existing environment to test the hypothesis of the culturally integrated labour delivery room design. The design outcome of a culturally design labour delivery room is still preliminary and require the will of policy makers to allow the practice of the Malay-Muslim into the clinical areas of the hospital from inception to the end. The outcomes require the reorganisation of the Labour Delivery Unit layout altogether and not just the labour delivery room in addressing the birthing culture. Malaysia is multi-culture. Studies had found out that there are similarities to each of these cultures in the birth event. Perhaps new hospitals may be able to experiment this new approach to the design. Adaptation may have to be made to existing LDUs if Malaysia is willing to Malaysianise the healthcare spaces and celebrates the new Malaysians with the value that culture brings into the modern healthcare environment.